Dynamics of myelination in the mammalian nervous system - Kaller, MS (2020)
Myelination was first understood to enable faster impulse propagation in axons more than 60 years ago, yet it took a long time to recognise the mechanistic complexity of this cellular process and the diverse roles that myelinating glia play in the formation and functioning of the vertebrate nervous system. Once considered a static insulator, myelinating glia are now increasingly recognised as dynamic and adaptive cell populations. The effective bidirectional signalling between axons and glia and dynamic changes in the Schwann cell population play a fundamental role in the injury response of the PNS. Furthermore, converging evidence now suggests that myelin in the CNS can be dynamically regulated by neuronal activity and continues to participate in nervous system plasticity beyond development, yet the functional role of such adaptive myelination remains unclear. While the dynamic natures and diverse functions of myelinating glia have now gained increased recognition, fundamental mechanisms and principles underlying these processes remain poorly understood. The aim of this thesis was to advance our understanding of myelin dynamics and the axon-glia communication regulating them. The first part of this thesis describes the development of myelinating co-cultures using human induced pluripotent stem cell-derived sensory neurons. Our work outlines how such a novel PNS co-cultures system can be used to provide insights into the cellular and molecular specialization of axoglial signalling, how pharmacological agents may promote or impede such signalling and the pathogenic effects of ganglioside antibodies. The second part of the thesis describes work aimed to investigate the role of neuregulin 1 (Nrg1) signalling in myelination in the PNS and CNS. While Nrg1 plays an essential role in the myelination of Schwann cells, as demonstrated in this thesis, its role in CNS myelination remains elusive. The work presented indicated that conditional global deletion of Nrg1 in mice leads to a behaviour deficit in a motor task. However, we found no conclusive evidence for a role of Nrg1 in adaptive myelination and myelinating glia dynamics in the CNS. The third part of this thesis focuses on the functional role of dynamic and adaptive myelination in the CNS, concentrating on the question if and how de novo myelination during adulthood facilitates and shapes motor behaviour and learning. The work presented replicates and extends previous findings indicating a causal relationship between adaptive myelination and behaviour change. However, not all aspects of evidence were faithfully replicated, and we conclude that further investigation is required to unravel the link between adaptive myelination and motor learning. Furthermore, our preliminary analysis of cellular and microstructural changes in CNS, acquired by combining histology and magnetic resonance imaging, remains partly inconclusive regarding the exact role that de novo myelination might play in skill acquisition. Overall, the major contributions of this thesis are the development of a novel and useful co-culture system using iPSC derived human cells and the thorough replication, critical evaluation and extension of important findings that indicated a causal link between myelin plasticity and behaviour change.